Application of the polynomial function method to the variable-coefficient Kadomtsev–Petviashvili equation - Xue-Sha Wu; Hao-Miao Zhang; Jian-Guo Liu (Results in Physics, 2023)
In this paper, we research a (2+1)-dimensional variable-coefficient Kadomtsev–Petviashvili equation in fluid dynamics and plasma physics. The lump, lump-soliton and lump-periodic solutions are derived based on the variable-coefficient polynomial function method. The effect of variable coefficients on the amplitude and velocity of solitons is analyzed and shown by some 3D graphs, contour plots and density graphs.